A method for preparing sulphoaluminate cement using aluminum ash
Patent Information
- Application Number
- CN202611119309.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]但是,铝灰成分复杂,活性不稳定,其中的氮化铝、金属铝等组分在遇水或碱性环境下容易发生反应并释放氨气、氢气等气体,氯盐、氟盐等可溶性杂质也可能影响水泥水化过程和硬化体耐久性,铝灰资源化利用的方法主要包括水洗除盐、酸浸或碱浸处理、高温焙烧等,但处理后铝灰的活性不足,利用附加值较低,尤其是在硫铝酸盐水泥制备领域,容易导致硫铝酸钙矿物生成不充分,进而影响水泥水化产物的形成和强度发展,若仅将铝灰作为普通铝源使用,往往难以兼顾铝灰无害化、熟料矿物形成效率、水泥早期强度和后期性能稳定性
1、本发明是将铝灰与氢氧化钠混合后进行动态高温碱焙烧,将铝灰中反应活性不稳定、有害或难以利用的含铝组分转化生成更易后续利用的铝酸钠类中间物,后续水提过程,通过二氧化碳中和残留强碱的同时,促使铝酸钠等水溶性铝酸盐发生水解、碳化和沉淀反应,使铝灰中的残余金属铝、氮化铝、可溶性盐及强碱性组分得到转化或去除,降低铝灰直接用于水泥体系时可能产生的放气、泛碱、异常凝结和体积不稳定问题,经过处理后,铝灰由反应不稳定的工业固废转化为较稳定的含铝原料,为后续硫铝酸钙矿物烧成提供铝源基础,并减少硬化体内部气泡孔和杂质缺陷,从而有利于提高胶砂试样的密实度、抗压强度和强度稳定性。
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of aluminum ash recycling technology, and more specifically to a method for preparing sulfoaluminate cement using aluminum ash. Background Technology
[0002] Sulfoaluminate cement is a special type of cement with calcium sulfoaluminate minerals as the main clinker minerals. It has the characteristics of high early strength, fast setting and hardening, micro-expansion, good impermeability and good low-temperature construction performance. Traditional sulfoaluminate cement is usually made from limestone, bauxite and gypsum as the main raw materials, and is produced by batching, calcination and grinding. Aluminum ash is a typical industrial solid waste generated in the process of aluminum smelting, aluminum processing and recycled aluminum production. It usually contains alumina, metallic aluminum, aluminum nitride, aluminum carbide, chloride salts, fluoride salts and other impurity components.
[0003] For example, reference publication number CN114890694A relates to cement materials based on the recycling of aluminum ash and their preparation methods. It mainly addresses the problem of aluminum ash polluting the environment while being unable to be rationally utilized. This cement material incorporates aluminum ash, a waste product generated in primary and secondary aluminum industries, with an aluminum content reaching up to 30%. 55%wt, aluminum ash is a renewable resource. Compared with bauxite, the usable aluminum content in aluminum ash far exceeds that of high-grade bauxite ore. Both metallic Al and AlN can be effectively utilized to convert into sulfoaluminate minerals, and SiO2 can provide some of the silicon element required by dicalcium silicate minerals. Therefore, aluminum ash can replace part of bauxite in the production of sulfoaluminate cement, which can not only greatly reduce raw material costs, but also realize the resource utilization of waste. By adding modifiers, the performance of aluminum ash-based cement materials can be greatly improved, promoting the development of aluminum ash-based cement materials.
[0004] However, aluminum ash has a complex composition and unstable activity. Components such as aluminum nitride and metallic aluminum are prone to react with water or alkaline environments, releasing gases such as ammonia and hydrogen. Soluble impurities such as chloride and fluoride salts may also affect the cement hydration process and the durability of the hardened body. The main methods for utilizing aluminum ash resources include water washing for desalination, acid or alkali leaching, and high-temperature calcination. However, the activity of the treated aluminum ash is insufficient, resulting in low added value. Especially in the field of sulfoaluminate cement preparation, it is easy to lead to insufficient formation of calcium sulfoaluminate minerals, which in turn affects the formation of cement hydration products and strength development. If aluminum ash is used only as a common aluminum source, it is often difficult to simultaneously achieve the harmlessness of aluminum ash, clinker mineral formation efficiency, early strength of cement, and stability of later performance.
[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing sulfoaluminate cement using aluminum ash, mainly addressing the technical problem that the early strength and later performance stability of sulfoaluminate cement mortar samples prepared from aluminum ash need to be further improved.
[0007] The objective of this invention can be achieved through the following technical solution: a method for preparing sulfoaluminate cement using aluminum ash, comprising the following steps: S1. After mixing aluminum ash with an alkaline calcining agent, alkaline calcination is carried out under an oxygen-containing atmosphere to obtain alkaline calcined aluminum ash. The alkaline calcined aluminum ash is mixed with water, and carbon dioxide is introduced into the reaction system for neutralization to make the pH of the system 5-7. After solid-liquid separation, washing, drying and calcination, detoxified aluminum ash is obtained. S2. Mix and pulverize the detoxifying aluminum ash, calcium source, copper source and phosphogypsum source, press and shape them and then perform aerobic calcination to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80μm. S3. Calcium sulfoaluminate, calcium sulfate setting regulator, alkaline activating component, active mineral admixture and polymer reinforcing agent are mixed evenly to obtain sulfoaluminate cement. The polymer reinforcing agent can form interfacial coupling and flexible branched network in the cement hydration system.
[0008] Furthermore, copper-modified calcium sulfoaluminate is obtained through the following steps: A1. Mix and pulverize the detoxifying aluminum ash, calcium source, copper source and phosphogypsum source, and pass through a 200-mesh sieve to obtain a mixture; A2. Add deionized water to the mixture, mix well, then press it into a mold to form a round cake, then calcine the round cake with oxygen, and after discharge, crush and sieve to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80μm.
[0009] Furthermore, in step A1, the ratio of the amounts of the detoxifying aluminum ash, calcium source, copper source, and phosphogypsum source is n. Al :n CaO :n CuO :n CaSO4 =6-7:4-5:0.1-0.2:1.1-1.5, wherein the calcium source is quicklime and the copper source is nano-copper oxide.
[0010] Further, in step A2, the solid-liquid ratio of the mixture and deionized water is 10:1, the diameter of the disc is 5 cm, the thickness is 1-2 cm, the pressing pressure is 3.1-3.6 MPa, and the aerobic roasting operation includes: transferring the disc to a muffle furnace, heating the muffle furnace to 850-950℃, holding it for roasting for 1-2 hours, then continuing to heat it to 1250-1300℃, holding it for roasting for 90-120 minutes, letting it cool naturally to room temperature, discharging the material, crushing the roasted disc and sieving it to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80 μm.
[0011] Furthermore, the preparation method of the polymer reinforcing agent is as follows: under the protection of an inert gas atmosphere, branched polysiloxane and toluene are mixed and stirred, the reaction system is heated to 70-80℃, propyltriethoxysilane isocyanate is added to the reaction system, the reaction is kept at the temperature for 40-60 min, and then post-processed to obtain the polymer reinforcing agent.
[0012] Furthermore, the ratio of the branched polysiloxane, toluene, and propyltriethoxysilane is 5-6g:20mL:1.1-1.3g, and the post-treatment includes: after the reaction is complete, the reaction system is heated to 80-90℃, and low-boiling substances are removed by vacuum evaporation to obtain the polymer reinforcing agent.
[0013] Further, the preparation method of branched polysiloxane is as follows: 3-glycidyl etheroxypropylmethyldiethoxysilane and polyethylene glycol are mixed and stirred, the reaction system is heated to 70-80℃ and kept at this temperature for 60-80 min, octamethylcyclotetrasiloxane is added to the reaction system, the reaction system is heated to 85-95℃, sulfuric acid is added to the reaction system, and the reaction is kept at this temperature for 4-5 h, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system, and the reaction is kept at this temperature for 60-80 min, followed by post-treatment to obtain branched polysiloxane.
[0014] Furthermore, the ratio of 3-glycidyl etheroxypropylmethyldiethoxysilane, polyethylene glycol, octamethylcyclotetrasiloxane, sulfuric acid, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1g:2g:5g:0.3-0.5mL:0.6-0.8g, and the sulfuric acid has a mass fraction of 80-90%. The post-treatment includes: after the reaction is complete, cooling the reaction system to 60-70℃, adding deionized water and toluene to the reaction system, stirring and dispersing for 5-8 minutes, allowing it to stand and separate the liquids, washing the upper organic phase with purified water until neutral at 60-70℃, and then removing low-boiling substances by vacuum evaporation at 80-85℃ to obtain branched polysiloxane.
[0015] Furthermore, the weight ratio of the copper-modified calcium sulfoaluminate, calcium sulfate setting agent, alkaline activating component, active mineral admixture and polymer reinforcing agent is 100:10-12:3-5:6-8:8-10.
[0016] Furthermore, the calcium sulfate setting regulator is selected from one or more of anhydrite, hemihydrate gypsum, and dihydrate gypsum; the alkaline activating agent is selected from one or more of hydrated lime, quicklime, and sodium carbonate; and the active mineral admixture is selected from one or more of blast furnace slag powder, metakaolin, silica fume, fly ash, and limestone powder.
[0017] The present invention has the following beneficial effects: 1. This invention involves mixing aluminum ash with sodium hydroxide and then subjecting it to dynamic high-temperature alkali roasting. This process transforms the unstable, harmful, or difficult-to-use aluminum-containing components in the aluminum ash into sodium aluminate intermediates that are easier to utilize. In the subsequent water extraction process, carbon dioxide neutralizes the residual strong alkali while promoting the hydrolysis, carbonization, and precipitation of water-soluble aluminates such as sodium aluminate. This process transforms or removes residual metallic aluminum, aluminum nitride, soluble salts, and strong alkaline components in the aluminum ash, reducing the potential problems of gas release, efflorescence, abnormal condensation, and volume instability that may occur when aluminum ash is directly used in cement systems. After treatment, the aluminum ash is transformed from an unstable industrial solid waste into a more stable aluminum-containing raw material, providing an aluminum source for the subsequent calcination of calcium sulfoaluminate minerals and reducing internal air bubbles and impurities in the hardened body. This, in turn, helps improve the density, compressive strength, and strength stability of the mortar sample.
[0018] 2. This invention further combines detoxifying aluminum ash, quicklime, nano-copper oxide, and phosphogypsum in a specific molar ratio, optimizing the aluminum, calcium, copper, and calcium sulfate sources to be within a suitable composition range for the formation of calcium sulfoaluminate as the main mineral. Phosphogypsum not only provides the sulfate and calcium sources required for the formation of calcium sulfoaluminate, but its trace phosphorus, fluorine, and silicon components can also form mineralization and fluxing effects during high-temperature firing, promoting the solid-phase reaction between detoxifying aluminum ash, quicklime, and nano-copper oxide, and increasing the degree of formation of active calcium sulfoaluminate minerals. Nano-copper oxide has a small particle size and high dispersibility, which can promote solid-phase diffusion and crystal phase rearrangement during high-temperature firing, increasing the degree of formation of active calcium sulfoaluminate minerals. Combined with pressing and staged aerobic calcination, it can balance firing uniformity, hydration activity, and mixing fluidity, enabling the copper-modified calcium sulfoaluminate to rapidly generate ettringite and alumina-based hydration products in the presence of calcium sulfate setting agent, forming an early load-bearing skeleton and improving the early compressive and flexural strength of the material.
[0019] 3. This invention also involves reacting epoxy-containing silanes, polyethylene glycol, cyclosiloxanes, and amino-terminated siloxanes to obtain branched polysiloxanes. These branched polysiloxanes are then reacted with isocyanate-based silanes to obtain a polymeric reinforcing agent. The polyethylene glycol segments in this polymeric reinforcing agent improve its dispersibility in cement paste, while the polysiloxane segments and branched structure reduce interparticle friction and provide steric hindrance. The hydrolyzable silane groups can adsorb, condense, or couple with hydration products or the surface of mineral particles, forming interfacial coupling and a flexible branched network in the cement hydration system. This improves mortar flowability and, during hardening, forms an organic-inorganic composite interfacial layer and a flexible reinforcing network, reducing defects in the interfacial transition zone and inhibiting microcrack propagation. Simultaneously, the alkaline activating component promotes the generation of secondary hydration products such as CSH and CASH from the active mineral admixtures, further filling pores and creating a dense structure. This allows sulfoaluminate cement to maintain good construction fluidity while achieving a synergistic improvement in early strength, flexural toughness, and 7-day strength. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0021] In this application, the sodium hydroxide is industrial grade, with an effective ingredient content of 98% and a particle size of 30-100 nm. In this application, the effective component content of the nano-copper oxide is 99.9%, and the particle size is 20-50 nm; In this application, the calcium sulfate dihydrate content in phosphogypsum is 93-95%, and the soluble phosphorus content is 1-2%. In this application, the polyethylene glycol is PEG-500 and the content of active ingredient is 99%.
[0022] Example 1 This embodiment provides a method for preparing sulfoaluminate cement using aluminum ash, specifically including the following steps: Step 1: Preparation of detoxifying aluminum ash Aluminum ash and sodium hydroxide were added in a weight ratio of 1:1 and placed in a rotary kiln. The rotation speed of the rotary kiln was set to 3 r / min. Under an air atmosphere, the rotary kiln was heated to 860℃, kept at the temperature for 120 min, and then cooled naturally to room temperature. The material was then discharged to obtain alkali-calcined aluminum ash. After pulverizing the alkaline-calcined aluminum ash, it was added to a reaction flask with purified water at a solid-liquid ratio of 1:5 and stirred. Carbon dioxide was introduced into the reaction flask to adjust the pH of the system to 5. The mixture was then filtered, and the filter cake was washed three times with purified water and transferred to a nitrogen-protected drying oven at 90°C. The cake was dried to constant weight and then calcined at 600°C for 4 hours to obtain detoxified aluminum ash.
[0023] Step 2: Preparation of copper-modified calcium sulfoaluminate The detoxifying aluminum ash, quicklime, nano copper oxide, and phosphogypsum were mixed in an n-fold ratio. Al :n CaO :n CuO :n CaSO4 The mixture of ingredients in the ratio 6:4:0.1:1.1 is thoroughly mixed, then pulverized and passed through a 200-mesh sieve to obtain the final mixture. Mix the mixture and deionized water at a solid-liquid ratio of 10:1 until homogeneous, then add it into a mold, set the molding pressure to 3.1 MPa, and press it into a round cake with a diameter of 5 cm and a thickness of 1 cm. The round cake was transferred to a muffle furnace, heated to 850℃, and roasted for 1 hour. Then, the temperature was increased to 1250℃ and roasted for 90 minutes. The cake was then allowed to cool naturally to room temperature and discharged. The roasted round cake was then crushed and sieved to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80 μm.
[0024] Step 3: Preparation of polymer reinforcing agent Weigh 10g of 3-glycidyl etheroxypropylmethyldiethoxysilane and 20g of polyethylene glycol into a reaction flask and stir. Heat the reaction flask to 70℃ and maintain the temperature for 60 min. Add 50g of octamethylcyclotetrasiloxane to the reaction flask and heat the reaction flask to 85℃. Add 3mL of 80wt% sulfuric acid to the reaction system and maintain the temperature for 4 h. Add 6g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to the reaction flask and maintain the temperature for 60 min. Cool the reaction flask to 60℃ and add 50mL of deionized water and 100mL of toluene to the reaction flask. Stir and disperse for 5 min. Allow to stand and separate the liquids. Wash the upper organic phase with purified water at 60℃ until neutral. Remove low-boiling substances from the organic phase under reduced pressure at 80℃ to obtain branched polysiloxane. Weigh out 50g of branched polysiloxane and 200mL of toluene and add them to a reaction flask under argon protection. Stir the mixture and heat the reaction flask to 70℃. Add 11-13g of propyltriethoxysilane isocyanate to the reaction flask and keep it at this temperature for 40min. Then heat the reaction flask to 80℃ and remove low-boiling substances by vacuum distillation to obtain the polymer reinforcing agent.
[0025] Step 4: Preparation of sulfoaluminate cement Anhydrite was chosen as the calcium sulfate setting regulator; Quicklime and hydrated lime are mixed in a weight ratio of 1:1 to obtain an alkaline activating component; Blast furnace slag powder was selected as the active mineral admixture. Weigh out the following components by weight: 100 parts calcium sulfoaluminate, 10 parts calcium sulfate setting regulator, 3 parts alkaline activating component, 6 parts active mineral admixture, and 8 parts polymer reinforcing agent. Mix them evenly to obtain sulfoaluminate cement.
[0026] Example 2 This embodiment provides a method for preparing sulfoaluminate cement using aluminum ash, specifically including the following steps: Step 1: Preparation of detoxifying aluminum ash Aluminum ash and sodium hydroxide were added in a weight ratio of 1:1 and placed in a rotary kiln. The rotation speed of the rotary kiln was set to 3.5 r / min. Under an air atmosphere, the rotary kiln was heated to 890℃ and kept at that temperature for 140 min. It was then allowed to cool naturally to room temperature and discharged to obtain alkali-calcined aluminum ash. After pulverizing the alkaline-calcined aluminum ash, it was added to a reaction flask with purified water at a solid-liquid ratio of 1:7.5 and stirred. Carbon dioxide was introduced into the reaction flask to adjust the pH of the system to 6. The mixture was then filtered, and the filter cake was washed three times with purified water and transferred to a nitrogen-protected drying oven at 95°C. The cake was dried to constant weight and then calcined at 650°C for 4.5 hours to obtain detoxified aluminum ash.
[0027] Step 2: Preparation of copper-modified calcium sulfoaluminate The detoxifying aluminum ash, quicklime, nano copper oxide, and phosphogypsum were mixed in an n-fold ratio. Al :n CaO :n CuO :n CaSO4 The mixture of 6.5:4.5:0.15:1.3 is thoroughly mixed, then pulverized and passed through a 200-mesh sieve to obtain the mixture. Mix the mixture and deionized water at a solid-liquid ratio of 10:1 until homogeneous, then add it to a mold, set the molding pressure to 3.3 MPa, and press it into a round cake with a diameter of 5 cm and a thickness of 1.5 cm. The round cake was transferred to a muffle furnace, heated to 900℃, and roasted for 1.5 hours. Then, the temperature was increased to 1275℃ and roasted for 105 minutes. The cake was then allowed to cool naturally to room temperature and discharged. The roasted round cake was then crushed and sieved to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80 μm.
[0028] Step 3: Preparation of polymer reinforcing agent Weigh 10g of 3-glycidyl etheroxypropylmethyldiethoxysilane and 20g of polyethylene glycol into a reaction flask and stir. Heat the reaction flask to 75℃ and maintain the temperature for 70 min. Add 50g of octamethylcyclotetrasiloxane to the reaction flask and heat the reaction flask to 90℃. Add 4mL of 85wt% sulfuric acid to the reaction system and maintain the temperature for 4.5 h. Add 7g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to the reaction flask and maintain the temperature for 70 min. Cool the reaction flask to 65℃ and add 50mL of deionized water and 100mL of toluene to the reaction flask. Stir and disperse for 6.5 min. Allow to stand and separate the liquids. Wash the upper organic phase with purified water at 65℃ until neutral. Remove low-boiling substances from the organic phase under reduced pressure at 83℃ to obtain branched polysiloxane. Weigh out 55g of branched polysiloxane and 200mL of toluene and add them to a reaction flask under argon protection. Stir the mixture and heat the reaction flask to 75°C. Add 11-13g of propyltriethoxysilane isocyanate to the reaction flask and keep it at this temperature for 50min. Then heat the reaction flask to 85°C and remove low-boiling-point substances by vacuum distillation to obtain the polymer reinforcing agent.
[0029] Step 4: Preparation of sulfoaluminate cement Hemihydrate gypsum was selected as the calcium sulfate setting regulator; Sodium carbonate was chosen as the alkaline activating component; Metakaolin was selected as the active mineral admixture; Weigh out the following components by weight: 100 parts calcium sulfoaluminate, 11 parts calcium sulfate setting regulator, 4 parts alkaline activating component, 7 parts active mineral admixture, and 9 parts polymer reinforcing agent. Mix them evenly to obtain sulfoaluminate cement.
[0030] Example 3 This embodiment provides a method for preparing sulfoaluminate cement using aluminum ash, specifically including the following steps: Step 1: Preparation of detoxifying aluminum ash Aluminum ash and sodium hydroxide were added in a weight ratio of 1:1 and placed in a rotary kiln. The rotation speed of the rotary kiln was set to 4 r / min. Under an air atmosphere, the rotary kiln was heated to 920℃, kept at the temperature for 160 min, and then cooled naturally to room temperature. The material was then discharged to obtain alkali-calcined aluminum ash. After pulverizing the alkaline-calcined aluminum ash, it was added to a reaction flask with purified water at a solid-liquid ratio of 1:10 and stirred. Carbon dioxide was introduced into the reaction flask to adjust the pH of the system to 7. The mixture was then filtered, and the filter cake was washed three times with purified water and transferred to a nitrogen-protected drying oven at 100°C. The cake was dried to constant weight and then calcined at 700°C for 5 hours to obtain detoxified aluminum ash.
[0031] Step 2: Preparation of copper-modified calcium sulfoaluminate The detoxifying aluminum ash, quicklime, nano copper oxide, and phosphogypsum were mixed in an n-fold ratio.Al :n CaO :n CuO :n CaSO4 The mixture of 7:5:0.2:1.5 is thoroughly mixed, then pulverized and passed through a 200-mesh sieve to obtain the mixture. Mix the mixture and deionized water at a solid-liquid ratio of 10:1 until homogeneous, then add it into a mold, set the molding pressure to 3.6 MPa, and press it into a round cake with a diameter of 5 cm and a thickness of 2 cm. The round cake was transferred to a muffle furnace, heated to 950℃, and roasted for 2 hours. Then, the temperature was increased to 1300℃ and roasted for 120 minutes. The cake was then allowed to cool naturally to room temperature and discharged. The roasted round cake was then crushed and sieved to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80 μm.
[0032] Step 3: Preparation of polymer reinforcing agent Weigh 10g of 3-glycidyl etheroxypropylmethyldiethoxysilane and 20g of polyethylene glycol into a reaction flask and stir. Heat the reaction flask to 80℃ and maintain the temperature for 80 min. Add 50g of octamethylcyclotetrasiloxane to the reaction flask and heat the reaction flask to 95℃. Add 5mL of 90wt% sulfuric acid to the reaction system and maintain the temperature for 5 h. Add 8g of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to the reaction flask and maintain the temperature for 60-80 min. Cool the reaction flask to 70℃ and add 50mL of deionized water and 100mL of toluene to the reaction flask. Stir and disperse for 8 min. Allow to stand and separate the liquids. Wash the upper organic phase with purified water at 70℃ until neutral. Remove low-boiling substances from the organic phase under reduced pressure at 85℃ to obtain branched polysiloxane. Weigh out 60g of branched polysiloxane and 200mL of toluene and add them to a reaction flask under argon protection. Stir the mixture and heat the reaction flask to 80℃. Add 13g of propyltriethoxysilane isocyanate to the reaction flask and keep the mixture at this temperature for 60min. Then heat the reaction flask to 90℃ and remove low-boiling substances by vacuum distillation to obtain the polymer reinforcing agent.
[0033] Step 4: Preparation of sulfoaluminate cement Gypsum dihydrate was selected as the calcium sulfate setting regulator. Quicklime and sodium carbonate are mixed in a weight ratio of 1:1 to obtain an alkaline activating component; Fly ash was selected as an active mineral admixture; Weigh out the following components by weight: 100 parts calcium sulfoaluminate, 12 parts calcium sulfate setting regulator, 5 parts alkaline activating component, 8 parts active mineral admixture, and 10 parts polymer reinforcing agent. Mix them evenly to obtain sulfoaluminate cement.
[0034] Comparative Example 1 The difference between this comparative example and Example 3 is that in step one, the preparation process of alkali-calcined aluminum ash is omitted, and aluminum ash is used instead of alkali-calcined aluminum ash to participate in the preparation of detoxifying aluminum ash.
[0035] Comparative Example 2 The difference between this comparative example and Example 3 is that no nano-copper oxide was added in step two.
[0036] Comparative Example 3 The difference between this comparative example and Example 3 is that the phosphogypsum in step two is replaced by anhydrite.
[0037] Comparative Example 4 The difference between this comparative example and Example 3 is that polyethylene glycol was not added in step three.
[0038] Comparative Example 5 The difference between this comparative example and Example 3 is that the branched polysiloxane in step 3 is used instead of the polymer reinforcing agent in step 4.
[0039] Performance testing: The flexural strength and compressive strength of test specimens prepared with sulfoaluminate cement prepared in Examples 1-3 and Comparative Examples 1-5 were determined according to the standard GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)" at the first day (1d), second day (2d), third day (3d) and seventh day (7d) of age. The flowability of test samples prepared using sulfoaluminate cements prepared in Examples 1-3 and Comparative Examples 1-5 was determined according to standard GB / T 2419-2005 "Method for Determination of Flowability of Cement Mortar". The performance test data are shown in Table 1 below.
[0040] Table 1 - Performance Test Data of Samples Data Analysis: Comparative analysis of the data in Table 1 shows that the mortar prepared with the sulfoaluminate cement of this invention has a fluidity of 183-189 mm. The test samples exhibited the following strengths at different ages: first day: flexural strength 7.6-8.1 MPa, compressive strength 49.6-52.1 MPa; second day: flexural strength 8.2-8.8 MPa, compressive strength 57.4-61.1 MPa; third day: flexural strength 9.1-9.6 MPa, compressive strength 65.2-69.4 MPa; and seventh day: flexural strength 9.6-10.5 MPa, compressive strength 73.5-79.6 MPa. All performance test data are superior to the comparative example. This invention describes a process involving dynamic high-temperature alkaline roasting with sodium hydroxide, carbon dioxide carbonization and neutralization, washing and drying, and secondary roasting. This process transforms unstable, harmful, or difficult-to-use aluminum-containing components in aluminum ash into stable and usable detoxified aluminum ash. Copper-modified calcium sulfoaluminate is then prepared using detoxified aluminum ash, phosphogypsum, quicklime, and nano-copper oxide as the main raw materials. Furthermore, it is compounded with setting regulators, alkaline activating components, mineral admixtures, and polymer reinforcing agents to form a sulfoaluminate cement system. This system improves the fluidity of cement mortar while utilizing aluminum ash and phosphogypsum resources, thereby enhancing the early strength, flexural strength, and later strength of cement mortar samples. It has significant environmental value and promising engineering application prospects.
[0041] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing sulfoaluminate cement using aluminum ash, characterized in that, Includes the following steps: S1. After mixing aluminum ash with an alkaline calcining agent, alkaline calcination is carried out under an oxygen-containing atmosphere to obtain alkaline calcined aluminum ash. The alkaline calcined aluminum ash is mixed with water, and carbon dioxide is introduced into the reaction system for neutralization to make the pH of the system 5-7. After solid-liquid separation, washing, drying and calcination, detoxified aluminum ash is obtained. S2. Mix and pulverize the detoxifying aluminum ash, calcium source, copper source and phosphogypsum source, press and shape them and then perform aerobic calcination to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80μm. S3. Calcium sulfoaluminate, calcium sulfate setting regulator, alkaline activating component, active mineral admixture and polymer reinforcing agent are mixed evenly to obtain sulfoaluminate cement. The polymer reinforcing agent can form interfacial coupling and flexible branched network in the cement hydration system.
2. The method for preparing sulfoaluminate cement using aluminum ash according to claim 1, characterized in that, Copper-modified calcium sulfoaluminate is obtained through the following steps: A1. Mix and pulverize the detoxifying aluminum ash, calcium source, copper source and phosphogypsum source, and pass them through a 200-mesh sieve to obtain a mixture; A2. Add deionized water to the mixture, mix well, then press it into a mold to form a round cake, then calcine the round cake with oxygen, and after discharge, crush and sieve to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80μm.
3. The method for preparing sulfoaluminate cement using aluminum ash according to claim 2, characterized in that, In step A1, the ratio of the detoxifying aluminum ash, calcium source, copper source, and phosphogypsum source is nAl:nCaO:nCaO:nCaSO4 = 6-7:4-5:0.1-0.2:1.1-1.5, the calcium source is quicklime, and the copper source is nano-copper oxide. In step A2, the solid-liquid ratio of the mixture and deionized water is 10:1, the diameter of the disc is 5 cm, the thickness is 1-2 cm, and the pressing pressure is 3.1-3.6 MPa. The aerobic roasting operation includes: transferring the disc to a muffle furnace, heating the muffle furnace to 850-950℃, holding it for roasting for 1-2 hours, then continuing to heat it to 1250-1300℃, holding it for roasting for 90-120 minutes, naturally cooling it to room temperature, discharging the material, crushing the roasted disc, and sieving it to obtain copper-modified calcium sulfoaluminate with a particle size of 20-80 μm.
4. The method for preparing sulfoaluminate cement using aluminum ash according to claim 1, characterized in that, The preparation method of the polymer reinforcing agent is as follows: under the protection of an inert gas atmosphere, branched polysiloxane and toluene are mixed and stirred, the reaction system is heated to 70-80℃, propyltriethoxysilane isocyanate is added to the reaction system, the reaction is kept at the temperature for 40-60 min, and then post-processed to obtain the polymer reinforcing agent.
5. The method for preparing sulfoaluminate cement using aluminum ash according to claim 4, characterized in that, The ratio of the branched polysiloxane, toluene, and propyltriethoxysilane is 5-6g:20mL:1.1-1.3g.
6. The method for preparing sulfoaluminate cement using aluminum ash according to claim 4, characterized in that, The preparation method of branched polysiloxane is as follows: 3-glycidyl etheroxypropylmethyldiethoxysilane and polyethylene glycol are mixed and stirred. The reaction system is heated to 70-80℃ and kept at this temperature for 60-80 min. Octamethylcyclotetrasiloxane is added to the reaction system, and the reaction system is heated to 85-95℃. Sulfuric acid is added to the reaction system and kept at this temperature for 4-5 h. 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added to the reaction system and kept at this temperature for 60-80 min. After post-treatment, branched polysiloxane is obtained.
7. The method for preparing sulfoaluminate cement using aluminum ash according to claim 6, characterized in that, The ratio of 3-glycidyl etheroxypropylmethyldiethoxysilane, polyethylene glycol, octamethylcyclotetrasiloxane, sulfuric acid, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1g:2g:5g:0.3-0.5mL:0.6-0.8g, and the sulfuric acid has a mass fraction of 80-90%.
8. The method for preparing sulfoaluminate cement using aluminum ash according to claim 1, characterized in that, The weight ratio of the copper-modified calcium sulfoaluminate, calcium sulfate setting regulator, alkaline activating component, active mineral admixture, and polymer reinforcing agent is 100:10-12:3-5:6-8:8-10.
9. A method for preparing sulfoaluminate cement using aluminum ash according to claim 1, characterized in that, The calcium sulfate setting regulator is selected from one or more of anhydrite, hemihydrate gypsum, and dihydrate gypsum; the alkaline activating agent is selected from one or more of hydrated lime, quicklime, and sodium carbonate; and the active mineral admixture is selected from one or more of blast furnace slag powder, metakaolin, silica fume, fly ash, and limestone powder.
Citation Information
Patent Citations
Cement material based on aluminum ash recycling and preparation method thereof
CN114890694A